2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4649164
|View full text |Cite
|
Sign up to set email alerts
|

Joint analysis of differential mobility spectrometer and mass spectrometer features for tuberculosis biomarkers

Abstract: In this article, we present results of recent efforts to identify biomarkers for tuberculosis using a differential mobility spectrometer (DMS). We focus specifically on the capability of exploiting a data collection system that employs a DMS in parallel with a mass spectrometer. This system permits previously developed algorithms for DMS to be used in conjunction with a device considered a gold-standard for chemical identification, making it a unique discovery tool for the determination of biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Another issue that would strength the utility of EB research in disease diagnose is the improvement of data fusion possibilities, developing tools to allow the merging of data obtained from different EB analysis approaches. Regarding this, Cunha et al identified putative biomarkers for tuberculosis exploiting a data collection system that uses a differential mobility spectrometer (DMS) in parallel with a MS. With this approach, they could use synergistically the statistical tools previously developed for DMS in MS chemical identification [ 274 ]. Nevertheless, more research is required to allow merger of data obtained using the state of art approaches (GC-MS and PTR-MS, for instance) with the more recent POC e-noses technologies.…”
Section: Data Analysis and Discriminatory Models Used In Breath Bimentioning
confidence: 99%
“…Another issue that would strength the utility of EB research in disease diagnose is the improvement of data fusion possibilities, developing tools to allow the merging of data obtained from different EB analysis approaches. Regarding this, Cunha et al identified putative biomarkers for tuberculosis exploiting a data collection system that uses a differential mobility spectrometer (DMS) in parallel with a MS. With this approach, they could use synergistically the statistical tools previously developed for DMS in MS chemical identification [ 274 ]. Nevertheless, more research is required to allow merger of data obtained using the state of art approaches (GC-MS and PTR-MS, for instance) with the more recent POC e-noses technologies.…”
Section: Data Analysis and Discriminatory Models Used In Breath Bimentioning
confidence: 99%